Simulação numérica de um escoamento turbulento não-reativo no interior de uma caldeira ciclônica industrial usando LES e URANS - Pereira, Luiz Gustavo Freitas (2021)
A numerical simulation of a non-reactive turbulent flow inside a cyclonic industrial CO boiler was investigated in order to understand the swirling formation, the fluid behavior in different locations inside the domain and the distribution of chemical species. As 80% of the energy matrix in Brazil is generated by combustion processes and government regulations about NOx emissions are becoming more restrict, enhancing combustion efficiency in a CO boiler with a turbulent swirling flow to reduce pollutant emissions has become an engineering research topic. Enhancing mixing processes through turbulent swirling flows might reduce thermal NOx formation. Computational fluid dynamics simulations were realized using the in-house MFSim code with the turbulent closure models LES, URANS Standard k − ", URANS Standard k − " Modified and URANS Realizable k − ". A theoretical basis about turbulence, LES and URANS closure models, mixing and swirling flows was provided. A state of art comprising different authors pointed out that some works with URANS Standard k − " demonstrated a premature solid-body rotation formation due to its eddy viscosity assumption and that swirling flows may reduce pollutant emissions by improving mixing of reactants and decreasing flame temperature. Validations concerning multi-component mixing flows and Immersed Boundary method were presented. From the results, LES and URANS Standard k − " presented similar velocity field results, capable of capturing the swirling formation. When analyzing three URANS closure models, a turbulent kinetic energy graph illustrated that it is relevant to observe the modeled part and the value obtained from velocity field fluctuations. The modified model presented low turbulent viscosity values and an LES-like behavior, with similar results to the standard model. The realizable model presented distant results comparing to the other models studied and there was no reverse flow in its swirling core. Adding different chemical species did not modify the velocity field and the highest mixing level was obtained in the most intense turbulent swirling region, close to the inlets. The data provided may assist in the comprehension of swirling formation, mixture processes inside a boiler and temperature control to reduce pollutant emissions